The following are two rules of transformations of functions:
• a·f(x), where a > 1, stretches the curve vertically by a factor of a.
,• f(x - r) moves the function r units right.
In this case, we have:
• Since the parent function is vertically stretched by a factor of 7 and 7 > 1, the equation for the new function is:
[tex]\begin{gathered} a=7 \\ f(x)=x \\ \text{ Then} \\ a\cdot f(x)=7x \\ g(x)=7x \end{gathered}[/tex]• Since the parent function shift right 9 units, the equation for the new function is:
[tex]\begin{gathered} r=9 \\ g(x-r)=7(x-9) \\ h(x)=7(x-9) \end{gathered}[/tex]AnswerThe equation of the new function is:
[tex]h(x)=7(x-9)[/tex]